Binder free platinum nanoparticles decorated graphene-polyaniline composite film for high performance supercapacitor application. (10th October 2017) - Sha, Rinky; Badhulika, Sushmee
Highlights: Simple, binder free Pt NPs decorated Gr-PANi based electrode for ultra-high performance supercapacitor application Pt-Gr-PANi composite was prepared by template-free electro-polymerization method followed by electro-deposition of Pt NPs FESEM image of composite revealed nano-fibrous structure of PANi with Pt NPs uniformly deposited on its surface Excellent specific capacitance with superior rate capability, charge storage capacity and cycling stability Abstract: Conventional supercapacitors use insulating binders with active materials for fabricating working electrodes. Use of such binder reduces electrical conductivity of the electrode, thus causing energy wastage of supercapacitor. To overcome this, herein, we report binder free Platinum (Pt) nanoparticles (NPs) decorated Graphene–Polyaniline (Gr-PANi) composite modified electrode for supercapacitor application. Pt decorated Gr-PANi composite was prepared by template-free electrochemical polymerization method followed by electro-deposition of Pt NPs. Detailed structural and chemical characterization of the composite were done by SEM, EDX spectroscopy and Raman scattering. FESEM image of Pt decorated Gr-PANi composite revealed nano-fibrous structure of PANi (average diameter of 50–100 nm) with Pt NPs uniformly deposited on its surface. Interconnected network of PANi nanofibers made matrix highly porous, thereby, providing an improved electrode/electrolyte interface area and shorter diffusion lengths for electrolytic ions. The electrochemical behavior of Pt NPs decorated Gr-PANi composite film was studied by cyclic voltammetry while galvanostatic charge–discharge measurements were carried out to investigate its capacitive performances. Pt decorated Gr-PANi composite based supercapacitor exhibited higher specific capacitance of 922.5 F/g which was ∼ 1.75 folds greater than that of only Gr-PANi based electrode at same current density (1 A/g) and much higher than previously reported Gr-PANi composite based supercapacitors. The developed Pt decorated Gr-PANi composite modified electrode exhibited charge capacity of 0.57 mAh/cm 2 and discharge capacity of 0.29 mAh/cm 2 which were 2.4 folds and 1.81 folds higher than only Gr-PANi electrode respectively. The significant improvement in specific capacitance with excellent sustainability to higher current, superior rate capability, charge storage capacity and cycling stability can be attributed to the synergistic effect of electrical double-layer capacitance and pseudocapacitance resulting from Gr and PANi respectively and excellent catalytic ability of Pt NPs. The as-synthesized Pt decorated Gr-PANi composite offers simple, promising and binder free electrode material for energy storage devices.